(untitled) (Research, Society and Development, 2022)
The objective of this study was to assess knowledge about epidemiology, sources of information and hygienic-sanitary conduct taken by individuals during the Covid-19 pandemic. This is an exploratory descriptive study with a quantitative, non-probabilistic and convenience approach. Data collection was performed online via the Google Forms platform. The questionnaire adopted had 37 questions and was of a structured, undisguised type. The sample was organized into three groups, according to the answer to the following question: “Have you had Covid-19? ” Yes, 11.4% (200); “didn’t have”, 59.6% (1,041), and “I don’t know”, with 29% (507). In all, 1,748 (100%) individuals were included in the study, with 11.4% (200) belonging to the group that had Covid-19, 59.6% (1,041) to those who did not, and 29% (507) to the group I don’t know, with the majority being female (64.5%). The age ranged from 18 to 66 years, with a mean of 25.3±7.9 years and a predominant age group of 18-22 years (51.9%). For 38% of the participants, social distancing was effective, 92% fully agreed that the elderly and people with chronic disease are a risk group for Covid-19 and 74.7% said that men were the most affected by the disease. The population was aware of the epidemiology of Covid-19, access to sources of information and hygienic-sanitary conduct.